The respiratory syncytial virus G protein conserved domain induces a persistent and protective antibody response in rodents. - Thien N Nguyen (PLoS ONE, 2012)
Respiratory syncytial virus (RSV) is an important cause of severe upper and lower respiratory disease in infants and in the elderly. There are 2 main RSV subtypes A and B. A recombinant vaccine was designed based on the central domain of the RSV-A attachment G protein which we had previously named G2Na (aa130-230). Here we evaluated immunogenicity, persistence of antibody (Ab) response and protective efficacy induced in rodents by: (i) G2Na fused to DT (Diphtheria toxin) fragments in cotton rats. DT fusion did not potentiate neutralizing Ab responses against RSV-A or cross-reactivity to RSV-B. (ii) G2Nb (aa130-230 of the RSV-B G protein) either fused to, or admixed with G2Na. G2Nb did not induce RSV-B-reactive Ab responses. (iii) G2Na at low doses. Two injections of 3 µg G2Na in Alum were sufficient to induce protective immune responses in mouse lungs, preventing RSV-A and greatly reducing RSV-B infections. In cotton rats, G2Na-induced RSV-reactive Ab and protective immunity against RSV-A challenge that persisted for at least 24 weeks. (iv) injecting RSV primed mice with a single dose of G2Na/Alum or G2Na/PLGA [poly(D,L-lactide-co-glycolide]. Despite the presence of pre-existing RSV-specific Abs, these formulations effectively boosted anti-RSV Ab titres and increased Ab titres persisted for at least 21 weeks. Affinity maturation of these Abs increased from day 28 to day 148. These data indicate that G2Na has potential as a component of an RSV vaccine formulation.